"The plastic cathedral": Innovation to extend the service life of a heritage structure. (8th December 2019) - Tanner, Peter; Lara, Carlos; Bellod, Juan L.; Sanz, David
Abstract: Due to its severely damaged condition, former La Laguna cathedral was demolished and rebuilt between 1905 and 1913, saving only its neo‐classical façade. Reinforced concrete, at the time an innovative technology, was deployed to expedite construction and reduce costs. The trade‐off for these benefits was the risk associated with the use of a scantily understood material. Although a reliability‐based assessment of the corrosion‐damaged load‐bearing system showed that structural safety requirements were fulfilled for the future service life, less than 100 years after its reconstruction, the temple was so profoundly deteriorated that the roof had to be replaced entirely. Reconstruction began on the healthy part of the existing columns, underneath the capitals. The solution adopted retains the geometry of the 1913 structure, while improving its ventilation and lighting as well as its aesthetics by reconfiguring the proportions as nearly as possible to the golden ratio. The ribs in the vaults and main dome, characteristic of the neo‐gothic style of the building, were built with self‐compacting concrete, reinforced with glass‐fiber polymer rebars, and joined monolithically to the shells, as well as to the existing walls and columns. The 0.08 m thick shells are also made of a relatively unknown material, self‐compacting concrete reinforced with polypropylene fibers. In order to reduce to acceptable levels the uncertainties associated with innovative technologies, in addition to laboratory tests, a full‐scale prototype of a typical dome was constructed prior to the execution of the new roof. Nearly a century after the previous, negative experience, thanks to modern structural engineering and materials science, new challenges can be assumed.